Benefits of Incubation on Divergent Thinking. Issue 3 (3rd July 2017) - Chiang, Noelle C.; Chen, Meng-Liang
Abstract : Studies on whether fixation cues provided in the first episode of divergent thinking tasks influence creative outcomes after incubation, as they do for convergent problem-solving tasks, remain limited. This research examined the beneficial effects of incubation using the delayed- and immediate-incubation paradigms. Participants in Experiment 1 were either provided or not provided fixation cues during the first episode of a new type of divergent-thinking task, similar to creating titles in plot stories. The results indicated that fixation cues moderated people's creative outcomes after incubation. Going through incubation did not improve the participants' creativity in the second episode for strong fixation cues. By contrast, an incubation period led to the generation of more divergent items in the second episode compared to the first episode for less strong fixation cues, and this led to the performance matching the condition without fixation cues. The results from Experiment 2 suggested that immediate incubation downsized the influence of fixation cues. Therefore, if people want to promote their creativity through a period of incubation, the outcomes may still depend on the conditions of environments in which the creative works are executed.